A Guide to EPA's Proposed Numeric Nutrient Water Quality Criteria for Florida - Thomas Obreza; Mark Clark; Brian Boman; Tatiana Borisova; Matt Cohen; Michael Dukes; Tom Frazer; Ed Hanlon; Karl Havens; Chris Martinez; Kati Migliaccio; Sanjay Shukla; et al. (EDIS)
SL316, a 9-page illustrated guide by Thomas Obreza, Mark Clark, Brian Boman, Tatiana Borisova, Matt Cohen, Michael Dukes, Tom Frazer, Ed Hanlon, Karl Havens, Chris Martinez, Kati Migliaccio, Sanjay Shukla, and Alan Wright, provides a basic, concise, and understandable description of the United States Environmental Protection Agency’s (EPA) proposed numeric nutrient criteria for Florida, the background events that led to its release, some pertinent scientific issues, and implications for the future. Published by the UF Department of Soil and Water Science, February 2010.